Note on the fractional Mittag-Leffler functions by applying the modified Riemann-Liouville derivatives - Kilicman, Adem; Saleh, Wedad (Sociedade Brasileira de Matematica, 2022)
In this article, the fractional derivatives in the sense of the modified Riemann-Liouville derivative is employed for constructing some results related to Mittag-Leffler functions and established a number of important relationships between the Mittag-Leffler functions and Wright function.